Pengaruh BOPO Dan NPF Terhadap Profitabilitas Bank Syariah Di Indoneisa - Iqra Wiarta; Dina Daniyanti; Etriya Etriya (Journal Development, 2016)
The main function of a bank is as an intermediary in the field of finance with the aim of being able to improve the welfare of the community without ignoring the goals of the founder or owner of the company and employees, namely profit growth from year to year. The main focus in this study is to determine and analyze the financial performance of PT. Bank Negara Indonesia Syariah for 5 years in the period 2011 to 2015 and analyzed the effect of the ratio of Operating Expenses on Operating Income (BOPO) and Non-Performance Funds on the ratio of Return On Equity (ROE). This research uses descriptive quantitative method with multiple linear regression analysis tool. The research data is secondary data obtained from the company's annual report for the period 2011 to 2015. The results showed that the company's financial performance from 2011 to 2015 always fluctuated, but showed positive performance with bank profits or profits every year in that period always showing an increase. Furthermore, the results of the analysis can be concluded that the BOPO and NPF ratios have no significant effect either simultaneously or partially on the ROE ratio with a significant level of 5%